Penerapan Prinsip Keterbukaan dalam Securities Crowdfunding sebagai Upaya Melindungi Investor dari Infomasi yang Menyesatkan - Asshidiq, Abdullah Widy (PUSKAPSI Law Review, 2023)
Abstrack The development of Digital Economy Technology produces Innovations in the field of Financial Technology. One of the developments in technological progress in the field of Fintech is the birth of Securities Crowdfunding. Securities Crowdfunding is a new financing method that differs from the conventional financial system because it considers the crowdfunding model to be formed by equity. In the development of increasingly advanced technology, it is necessary to protect the interests of investors as an effort to maintain trust and the crowdfunding securities market. therefore the application of the principle of transparency is necessary in order to protect investors in making business decisions. This study uses a normative method with a statutory approach to determine the application of the Principle of Disclosure. In Securities Crowdfunding The principle of transparency is necessary to protect investors from false information. Keywords: Securities Crowdfunding, Disclosure Principle, Investors, false information. Abstrak Perkembangan Teknologi Ekonomi Digital menghasilkan Inovasi di bidang Finansial Teknologi. Salah satu perkembangan nya kemajuan teknologi di bidang Fintech adalah lahir nya Securities Crowdfunding, Securities Crowdfunding adalah metode pembiayaan baru yang berbeda dari sistem keuangan konvensional karena menganggap model crowdfunding dibentuk Ekuitas. dalam perkembangan teknologi yang semakin maju maka perlu untuk melindungi kepentingan investor sebagai upaya menjaga kepercayaan dan pasar securities crowdfunding. maka dari itu penerapan prinsip keterbukaan diperlukan guna untuk melindungi investor dalam mengambil keputusan bisnis. Penelitian ini menggunakan metode normatif dengan pendekatan perundang-undangan untuk mengetahui penerapan Prinsip Keterbukaan.Pada Securities Crowdfunding Prinsip keterbukaan perlu dilakukan guna melindungi investor dari informasi palsu. Kata Kunci: Securities Crowdfunding, Prinsip Keterbukaan, Investor, informasi palsu.